PENGKLUSTERAN DATA TIME SERIES KEUANGAN DENGAN MODEL GARCH (1,1) PADA PASAR SAHAM INTERNASIONAL - Rafulta, Elfa (Sainstek : Jurnal Sains dan Teknologi, 2012)
paper introduced a method clustering for financial data. By using the model Heteroskidastity Generalized autoregressive conditional (GARCH), will be estimated distance between the stock market using GARCH-based distance. The purpose of this method is mengkluster international stock markets with different amounts of data. Keywords: GARCH, Cluster Analisis, Intenational Stock Markets